Evaluating the seismic behaviour of rammed earth buildings from Portugal: From simple tools to advanced approaches - Silva, Rui André Martins (2018)
Despite the use of rammed earth became marginal in the second half of the past century, Portugal still holds an important built heritage. Recently, a growing use of rammed earth has been observed in modern constructions, but it is putting aside the roots of traditional rammed earth construction. The seismic behaviour of rammed earth buildings is still insufficiently comprehended, constituting a matter of great concern, since most of the traditional dwellings are built on regions with important seismic hazard. Moreover, the complex architecture of modern rammed earth buildings is expected to make their seismic behaviour even more fragile. This paper intends to provide a better comprehension on the seismic behaviour of rammed earth constructions from Portugal. For this purpose, twenty traditional dwellings were evaluated on the basis of a simplified approach, while a modern construction was investigated by means of destructive and non-destructive testing approaches. The main findings of these approaches are discussed in detail, but it can be highlighted that the architectural features of traditional rammed earth buildings benefit their seismic behaviour, while the complex architecture of modern rammed earth buildings demands using advanced engineering tools for their seismic assessment.